2016
DOI: 10.1111/hsc.12398
|View full text |Cite
|
Sign up to set email alerts
|

Older UK sheltered housing tenants' perceptions of well-being and their usage of hospital services

Abstract: The aim of this study was to examine sheltered housing tenants' views of health and well-being, the strategies they adopted to support their well-being, and their use of health and social care services through a Health Needs Assessment. Sheltered housing in the UK is a form of service-integrated housing for people, predominantly over 60. The study used a parallel, three-strand mixed method approach to encompass the tenants' perceptions of health and well-being (n = 96 participants), analysis of the service's h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 15 publications
1
25
1
Order By: Relevance
“…As the cross‐sectional nature of this study limits the possibility to determine which features of sheltered housing may be associated with thriving, previous international research may provide insight into the features that are seen as beneficial among residents in sheltered housing. Although international comparisons between sheltered housing are challenging due to the current conceptual ambiguity concerning accommodation models for older people, there seem to be considerable similarities in sheltered housing in Europe, such as the intention of independent living, increased accessibility of apartments, shared facilities, and the provision of opportunities to social interaction (Cook et al, ; Herbers & Meijering, ; Iecovich, ; van Bilsen et al, ), which is why the studies selected for comparison are based in Europe. A UK study from 2016, based on group interviews with 96 sheltered housing tenants, has shown that those residing in sheltered housing in the UK feel a heightened responsibility for their own health, which is attributed to the social support received in sheltered housing (Cook et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As the cross‐sectional nature of this study limits the possibility to determine which features of sheltered housing may be associated with thriving, previous international research may provide insight into the features that are seen as beneficial among residents in sheltered housing. Although international comparisons between sheltered housing are challenging due to the current conceptual ambiguity concerning accommodation models for older people, there seem to be considerable similarities in sheltered housing in Europe, such as the intention of independent living, increased accessibility of apartments, shared facilities, and the provision of opportunities to social interaction (Cook et al, ; Herbers & Meijering, ; Iecovich, ; van Bilsen et al, ), which is why the studies selected for comparison are based in Europe. A UK study from 2016, based on group interviews with 96 sheltered housing tenants, has shown that those residing in sheltered housing in the UK feel a heightened responsibility for their own health, which is attributed to the social support received in sheltered housing (Cook et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although international comparisons between sheltered housing are challenging due to the current conceptual ambiguity concerning accommodation models for older people, there seem to be considerable similarities in sheltered housing in Europe, such as the intention of independent living, increased accessibility of apartments, shared facilities, and the provision of opportunities to social interaction (Cook et al, ; Herbers & Meijering, ; Iecovich, ; van Bilsen et al, ), which is why the studies selected for comparison are based in Europe. A UK study from 2016, based on group interviews with 96 sheltered housing tenants, has shown that those residing in sheltered housing in the UK feel a heightened responsibility for their own health, which is attributed to the social support received in sheltered housing (Cook et al, ). A questionnaire study from the Netherlands, with a sample of 317 older people at risk of institutionalization, out of which 179 were living in sheltered housing, showed that those residing in sheltered housing reported experiencing greater autonomy, as well as feeling safer and less vulnerable when being outside and home alone, compared with those ageing in place (van Bilsen et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations